The therapeutic potential of natural products for treating pancreatic cancer - He, Xia; Wang, Ning; Zhang, Yu; Huang, Xiaobo; Wang, Yi (Frontiers in Pharmacology, 2022)
Pancreatic cancer is one of the most common malignant tumors of the digestive tract, with the poor prognosis and low five-year survival rate less than 10%. Meanwhile, pancreatic cancer has insidious and atypical clinical symptoms, making it difficult to be diagnosed and therapied. Approximately 90% of them are ductal adenocarcinomas originating from glandular epithelium. Its morbidity and mortality have increased significantly in recent years. Therefore, there is an urgent need to develop alternative strategies for its treatment. In this review, the pathological process and therapeutic targets of pancreatic cancer were addressed, including the surgical resection, immunotherapy and targeted therapy. However, the overall survival rates of pancreatic cancer are quite low due to drug resistance. Hence, in this review, we summarized the major natural products under investigation, including toosendanin, triptolide, libertellenone H, propolis, and etc. These compounds with antiviral, anti-inflammatory, antioxidant, anti-angiogenic and anti-metastatic activities can inhibit the formation of pancreatic cancer. Expecting to provide comprehensive information of potential natural products for pancreatic cancer treatment, our review provides valuable information and strategies for pancreatic cancer researchers and clinicians.